Perbedaan Parameter Hematologi Neutrophil to Lymphocyte Ratio (NLR) Antara Pasien Diabetes Melitus dan Tanpa Diabetes Melitus berdasarkn Derajat Keparahan Sakit Covid-19 - Luse Loe; Nanny Natalia Mulyani Soetedjo; Hikmat Permana; Bachti Alisjahbana (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2025)
Background: Patients with diabetes mellitus (DM) have higher risk of complications caused by coronavirus 2019 (COVID-19). COVID-19 virus causes leukopenia and lymphopenia. The neutrophil to lymphocyte ratio (NLR) is a parameter in the complete blood count routinely performed on admission. Method: This study aims to evaluate the difference between NLR in diabetic and non-diabetic patients based on COVID-19 severity. This is a cross-sectional, retrospective, descriptive-analytical study, and the analysis was performed using the comparison test in COVID-19 patients admitted to Hasan Sadikin Hospital from March 2020 to March 2021 using secondary data collected from medical records. There were 612 subjects included in this study. Result: We found a higher NLR median in diabetic (4.1, IQR 2.3-6.2) than non-diabetic (2.9, IQR 2.0-4.0) subjects, with p<0.001. Increased NLR was seen in diabetic COVID-19 subjects with mild to moderate severity, median NLR in diabetic group 4.1 (IQR: 2.3-6.2) vs 2.9 (IQR: 2.0-4.0) in non-diabetic group (p=<0.001). The median NLR was significantly higher in severe-critical diabetic subjects (4.8, IQR 3.0-6.8) than in mild-moderate non-diabetic subjects (2.9, iQR 2.0-4.0). Conclusion: NLR differs between the diabetic and non-diabetic groups depending on the severity of the disease. The NLR is an important parameter in assessing the severity of disease in COVID-19.